Determinants of Anxiety, Stress, and Depression of Nurses during the COVID-19 Pandemic of Omicron Variant - Lisna Anisa Fitriana; Lena Helen Supriatna; Mery Tania (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2022)
ABSTRACT.Introduction. The Omicron variant is a new variant of the Coronavirus which is thought to be able to spread and infect humans faster than the previous variant. The rapid transmission of the disease and the high mortality cause great panic and anxiety not only for the general public but also in the health sector. One of the health workers who are very vulnerable to receiving the impact of the emergence of COVID-19 is nurses. In addition to being directly infected, psychological disorders such as anxiety, stress, and depression are very easily experienced by nurses due to various causes. Objective. The purpose of this study was to know the determinants of the anxiety, stress, and depression of nurses during the COVID-19 pandemic of the Omicron variant. Method.  The research method is a quantitative study with a cross-sectional approach. This research was conducted in the adult inpatient room at the RSUD Kota Bandung in February 2022. The respondents were 64 nurses with a total sampling technique. The research instrument used a Depression Anxiety Stress Scale-42 (DASS-42) questionnaire which was collected via a google form. The data were analyzed using Pearson chi square test. Result. The results showed that a small proportion of nurses experience mild to moderate anxiety, stress, and depression. The bivariate test showed that there was no significant relationship between age, gender, education, and length of work with anxiety, stress, and depression (p0.05) in nurses in the adult inpatient room at the RSUD Kota Bandung. Discussion. Although small, there are still nurses who experience stress, anxiety, and depression, so the hospital should provide training on how to deal with anxiety, stress, and depression for nurses so that nurses have adaptive coping mechanisms when anxiety, stress, or depression occurs. ABSKTRAK.Pendahuluan. Varian Omicron merupakan varian baru dari Virus Corona yang diperkirakan mampu menyebar dan menginfeksi manusia lebih cepat dari varian sebelumnya. Penularan penyakit yang cepat dan angka kematian yang tinggi menimbulkan kepanikan dan kecemasan yang besar tidak hanya bagi masyarakat umum tetapi juga di bidang kesehatan. Salah satu tenaga kesehatan yang sangat rentan menerima dampak dari munculnya COVID-19 adalah perawat. Selain tertular secara langsung, gangguan psikologis seperti kecemasan, stres, dan depresi sangat mudah dialami oleh perawat karena berbagai penyebab. Tujuan. Tujuan penelitian ini untuk mengetahui determinan kecemasan, stres, dan depresi perawat selama pandemi COVID-19 varian Omicron. Metode. Metode penelitian yang digunakan adalah penelitian kuantitatif dengan pendekatan cross sectional. Penelitian ini dilakukan di ruang rawat inap dewasa RSUD Kota Bandung pada bulan Februari 2022. Respondennya adalah 64 perawat dengan teknik total sampling. Instrumen penelitian menggunakan kuesioner Depression Anxiety Stress Scale-42 (DASS-42) yang dikumpulkan melalui google form. Analisis data menggunakan uji pearson chi square. Hasil. Hasil penelitian menunjukkan sebagian kecil perawat mengalami kecemasan, stres, dan depresi ringan sampai sedang. Uji bivariat menunjukkan bahwa tidak ada hubungan yang signifikan antara usia, jenis kelamin, pendidikan, dan lama kerja dengan kecemasan, stres, dan depresi (p0,05) pada perawat di ruang rawat inap dewasa RSUD Kota Bandung. Diskusi. Meskipun kecil, namun masih ada perawat yang mengalami cemas, stress, dan depresi, sehingga sebaiknya pihak rumah sakit memberikan pelatihan mengenai cara mengatasi kecemasan, stress, dan depresi bagi perawat agar perawat memiliki mekanisme koping adaptif saat terjadi kecemasan, stress, ataupun depresi.